Solid Waste Management Practice and Health Implication: A Case of Kathmandu Metropolitan City, Nepal - Pandey, Rishikesh (Himalayan Review, 2009)
Waste handling practice in Kathmandu is labor intensive and disposal system does not meet environmental standard. Mixture of organic to inorganic and hazardous to non-hazardous wastes is the composition of municipal waste of Kathmandu. Waste management practice has severe health impact to municipal waste workers. Over the past several generations, people of specific castes (Pode, Chyame) have been working as municipal waste workers and are entitled ‘kuchikar' officially. This research examines occupational health problems of these waste workers. Findings are based on the survey of 61 waste workers of Kathmandu Metropolitan City. Key words: Environmental problems, waste management, occupational health, waste workers, protective measures. The Himalayan Review 35-36 (2004-2005) 33-47